Ashcroft model potential study of lattice dynamics of α-Iron and barium - Boselli, M. A.; Shukla, M. M. [UNESP] (My University, 1999)
Ashcroft model potential has been used to compute phonon dispersion relations along the three principal symmetry directions, i.e. [k00], [kk0] and [kkk] for α-iron and barium. The computed phonons gave a reasonable agreement with the experimental ones in all the three principal summetry directions expect for the T2 branch in [KK0] direction where the present study failed to reproduce the experimental findings.
Keywords: Ashcroft potential; Barium; Lattice dynamics; α-iron